2014
DOI: 10.2147/opth.s57086
|View full text |Cite
|
Sign up to set email alerts
|

Progressive retinal detachment secondary to juxtapapillary microholes in association with type 3 posterior staphylomas

Abstract: PurposeThis study describes a novel subtype of retinal detachment occurring in eyes with pathological myopia associated with type 3 posterior staphyloma and discusses the management options.MethodsWe retrospectively reviewed the case notes of seven patients who presented with unilateral symptomatic rhegmatogenous retinal detachment secondary to nasal juxtapapillary microholes.ResultsAll seven patients had pathological myopia and an associated peripapillary type 3 posterior staphyloma. They all presented with s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…articles were the analyses of congenital peripapillary changes,[17][18][19][20] and only one article was a report about a peripapillary staphyloma associated with high myopia 21. …”
mentioning
confidence: 99%
“…articles were the analyses of congenital peripapillary changes,[17][18][19][20] and only one article was a report about a peripapillary staphyloma associated with high myopia 21. …”
mentioning
confidence: 99%
“…Dinah et al 9 treated a cases series of three patients with RD in high myopic eyes with posterior breaks with silicone oil, and in two eyes the silicone oil was never removed.…”
Section: Discussionmentioning
confidence: 99%
“…Chen et al 10 and Dinah et al 9 proposed an internal approach to RD in high myopic eyes associated with paravascular or juxtapapillary retinal microhole using laser retinopexy around the breaks and long-term gas tamponade with good anatomical results.…”
Section: Discussionmentioning
confidence: 99%
“…Benson and Tasman [13] first reported three cases of rhegmatogenous RD caused by paravascular vitreoretinal traction. Dinah et al [7] reported 7 cases of juxtapapillary microholes in high myopic eyes associated with type 3 posterior staphyloma. In all these 7 cases, there was a single hole located within the peripapillary chorioretinal atrophic area, and shallow and stable RD developed shortly after the onset of posterior vitreous detachment.…”
Section: Discussionmentioning
confidence: 99%
“…Retinal detachment (RD) with posterior breaks in highly myopic eyes has been reported in previous studies [6][7][8]. However, whether the breaks were related to PVAs was never reported.…”
Section: Introductionmentioning
confidence: 94%